HIFI Media Berbasis ICT untuk Pembelajaran SKI - Firmansah, Defi; Agustina, Ulfa Wulan; Rohmah, Hidayatur; Ummah, Amalia Choiru (Institut Agama Islam Sumatera Barat, 2023)
This research is development research (Research and Development) that aims to determine the development of ICT-based learning media for SKI learning. The research subjects were students of class 10 IPA 5 at SMA DU 1 Jombang, totaling 30 students. This type of research is R&D with the ADDIE model which includes 5 phases. Islamic Cultural History learning media utilizes the I-Spring Suite after it has been created, approved, and reproduced and has gone through several modifications to present SKI learning media that are suitable for use. Collecting data using observation, and questionnaires. Validation questionnaires were assessed by material experts and media experts. The assessment uses a Likert scale with conditions such as strongly agree, agree, disagree, and strongly disagree. The results of the validation assessment from material expert 1 were 75% and material expert 2 was 76% in the good category, the validation assessment from media expert 1 was 75% and media expert 2 was 88% in the very good category. Meanwhile, through the response questionnaire, the average rating generated is 80% with a good category